A Convenient Synthesis of Tetrasubstituted Pyrazoles from Nitrile Imines and 2-(Thioxothiazolidin-5-ylidene)acetates - Yavari, Issa; Taheri, Zohreh; Naeimabadi, Maryam; Bahemmat, Samira; Halvagar, Mohammad Reza (Synlett, 2018)
Alkyl 2-(3-alkyl-4-oxo-2-thioxothiazolidin-5-ylidene)acetates react with hydrazonoyl chlorides in the presence of triethylamine to afford tetrasubstituted pyrazole derivatives. Formally, this transformation is regarded as a 1,3-dipolar cycloaddition of the exocyclic carbon–carbon double bond of the thioxothiazolidine derivatives with nitrile imines generated in situ. This efficient method provides fast access to a range of structurally diverse pyrazoles. The structure of a typical product is confirmed by X-ray crystallography.
Keywords: nitrile imines; 1,3-dipolar cycloaddition; regioselective; tetrasubstituted pyrazoles; X-ray crystallography